2010
DOI: 10.1007/s10482-010-9517-2
|View full text |Cite
|
Sign up to set email alerts
|

Wickerhamomyces anomalus in the sourdough microbial ecosystem

Abstract: We previously found that Wickerhamomyces anomalus (formerly Hansenula anomala, Pichia anomala) was the second most frequently isolated yeast in Belgian artisan bakery sourdoughs and that the yeast dominated laboratory sourdough fermentations. Such findings are of interest in terms of the advantage of W. anomalus over other commonly encountered sourdough yeasts and its potential introduction into the sourdough ecosystem. Here, we provide a brief overview of current knowledge on yeast ecology and diversity in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 51 publications
1
33
0
2
Order By: Relevance
“…Despite W. anomalus being found commonly in artisan bakery sourdoughs (14), to the best of our knowledge no reports have previously considered its use as a starter for sourdough fermentation (15). The bread manufactured with the combination of L. plantarum 1A7 and W. anomalus LCF1695 showed the most volume and softness, and in a sensory analysis, it was appreciated for elasticity, color, and overall taste.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Despite W. anomalus being found commonly in artisan bakery sourdoughs (14), to the best of our knowledge no reports have previously considered its use as a starter for sourdough fermentation (15). The bread manufactured with the combination of L. plantarum 1A7 and W. anomalus LCF1695 showed the most volume and softness, and in a sensory analysis, it was appreciated for elasticity, color, and overall taste.…”
Section: Discussionmentioning
confidence: 89%
“…Ethanol is also permitted as an antifungal preservative (2% [wt/wt]). Its inhibitory effect varies depending on the fungal species, and in some cases, it is not sufficient to prevent contamination (14).Several studies have focused on the antifungal activity of compounds from natural sources and on biopreservation as effective alternatives to chemical preservatives. Several antimicrobial compounds have been identified, especially proteins or peptides from plants, as well as metabolites derived from fermentation by lactic acid bacteria (12,23,25,42,43).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported from sourdoughs and was found as the dominating yeast in sourdough microbial ecosystems next to S. cerevisiae. The prevalence of the fungus was associated with its osmotolerance and increased acid tolerance in comparison to S. cerevisiae [22]. Furthermore, it was shown that W. anomalus provides some antimicrobial activity, e.g., mycocin production, that can be used to prolong the shelf life of bread [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…다양한 야생 효모종에 의한 제빵연구는 주로 해외에서 많이 수행되어, 미국의 SanFransisco sour dough 및 이탈리아의 Pannetoni bread 등 [20]에는 S. exiguus 및 Candida milleri가, 벨 기에 Artisan bakery의 sour dough [5]에는 Wickerhamomyces anomalus등이 사용되며, 독일의 sour dough에는 S. cerevisiae, Pichia saitoi, C. krusei, Torulopsis holii 등 [13] Relative CO 2 production(%) Fig. 4.…”
unclassified